2022
DOI: 10.18006/2022.10(6).1453.1461
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foliar application with Moringa oleifera residue fertilizer on growth, and yield quality of leafy vegetables

Abstract: Biofertilizers produced from organic materials help to promote the growth, and yield quality of crops and is more environmentally friendly than chemical fertilizers. Moringa oleifera is a leafy vegetable whose leaves are also used to make biofertilizers. The use of moringa non-edible parts in biofertilizer preparation remains under-explored. In this study, a procedure to produce moringa foliar biofertilizer (MFB) from non-edible parts was developed. The effect of composting time (3 to 4 months) on the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The foliar application of tree leaf extracts increased yield and nutrition of black gram, due to the presence of microelements and plant growth regulators likely iron, calcium and potassium, amino acids, ascorbic acid, phenolics and Zeatin [10]. Similar observation was recorded by Chanthanousone et al [16] in lettuce and spinach and Irshad et al [17] in chickpea. The Control treatment recorded lower yield.…”
Section: Grain Yieldsupporting
confidence: 74%
See 1 more Smart Citation
“…The foliar application of tree leaf extracts increased yield and nutrition of black gram, due to the presence of microelements and plant growth regulators likely iron, calcium and potassium, amino acids, ascorbic acid, phenolics and Zeatin [10]. Similar observation was recorded by Chanthanousone et al [16] in lettuce and spinach and Irshad et al [17] in chickpea. The Control treatment recorded lower yield.…”
Section: Grain Yieldsupporting
confidence: 74%
“…Moringa, bael, notchi, and Albizia amara tree leaf extracts have nutritional, insecticidal, and fungicidal properties [14]. Similarly, the tree leaf extracts had improved the growth and yield of the crops [15,14,16,17]. However, the standardization of various leaf extracts with effective concentration is need to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The leaf area index (LAI) is the sum of the leaf area from all plants divided by the ground area. Yield components included: (i) fresh mass per plant (g/plant) (including the stems, leaves and roots); (ii) theoretical yield (tons per ha) (average fresh mass/plant × plant density); (iii) actual yield (tons per ha) was also estimated (Chanthanousone et al 2022). Statistical analysis was performed by one-way analysis of variance (ANOVA), followed by Tukey's test, using the SPSS statistic 20.0 software (SPSS Inc., Chicago, IL, USA).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…These materials can be utilized to generate Moringa organic fertilizer. Previous studies indicated that applying Moringa foliar biofertilizer produced from nonedible parts promotes the growth, yield, ascorbic acid content and Brix of lettuce (Chanthanousone et al 2022). This study aimed to evaluate the effect of the incubation period on the Moringa residual organic fertilizer and its impact on the growth of lettuce and mustard spinach in Thua Thien Hue province, Vietnam.…”
Section: Introductionmentioning
confidence: 99%